PERI-PROCEDURAL OUTCOME OF SAPHENOUS VEIN GRAFT INTERVENTION - Shakoor, Tariq; Mallick, Nadeem Hayat; Noeman, Ahmad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Patients who develop recurrent myocardial ischemia after coronary artery bypass graft (CABG) surgery are often referred for percutaneous coronary intervention. The objective of this study was to evaluate the clinical characteristics and peri-procedural outcomes in patients with prior CABG referred for percutaneous coronary intervention (PCI) over a 3 year period. Methods: Data were collected on patients who underwent coronary interventional procedures following CABG surgery. We evaluated angiographic procedural success and immediate outcome among patients who had undergone such procedures from Nov 2006 to Oct 2009 (n=113). Results: Patients in the 2006- 2009 cohort had mean age 58.2 years, more patients were male (109 vs 4) and were more likely to have hypertension (57.5%), hyperlipidaemia (72.6%) and family history of ischemic heart disease (IHD) (65.5%), but less likely to have smoking (42.5%). Acute closure of stent leading to procedural failure was seen in 1 (0.9%) patient, sub-acute thrombosis of stent was seen in 1 (0.9%) patient, dissection or perforation of target vessel was seen in 3 (2.7%) and 1 (0.9%) patients respectively. Slow flow phenomenon was seen in 13 (11.5%) and post-procedural cardiac enzymes were raised in 6 (5.3%) patients. Conclusion: Success rates of saphenous vein graft (SVG) intervention and survival rate have improved with time as a result of improvements in technique and greater use of stents, filter devices and adjunctive medications. Keywords: Percutaneous coronary intervention, saphenous vein graft, Ischemic heart disease, IHD